Pengaruh Effleurage Massage terhadap Nyeri Persalinan Kala I Fase Aktif di Praktik Mandiri Bidan Nuriman Rafida dan Praktik Mandiri Bidan Latifah Kota Jambi Tahun 2019 - Herinawati Herinawati; Titik Hindriati; Astrid Novilda (Universitas Batanghari Jambi, 2019)
One of the complaints that is often felt by mothers is pain during contractions and effleurage massage is one technique that can cause the effects of distraction and relaxion, thus helping the mother become more relaxed, creating a feeling of comfort, and pain response will decrease. The purpose of this study was to determine the effect of effleurage massage on labor pain in the first stage in the practice of Midwife Nuriman Rafida and Latifah Midwife Practice in 2019. The sampling technique used a total sampling technique that was as many as 30 women who had labor pain. The level of pain during the active phase I before the massage effleurage: 16 (53.0%) respondents experienced moderate pain levels and 14 (47.0%) respondents experienced severe pain levels, and none experienced mild pain. The level of pain during the first active phase after effleurage massage: most (57.0%) respondents felt mild pain, still some (33%) respondents who felt moderate pain, and only a small percentage (10%) of respondents felt severe pain. The results of the Wilcoxon test showed that giving effleurage massage had a significant effect on pain when I was active phase P value was 0.001 (p<0.05).